Hoạt tính diệt khuẩn của nano bạc và nanocompozit Ag/Al2O3 được kết tủa điện hóa. - Phúc, Nguyễn Công; Hùng, Nguyễn Đức (Vietnam Journal of Chemistry, 2012)
Anodic aluminium oxide (AAO) membrane has uniform parallel pores and high pore density. The pore diameter is controllable according to practical needs. Ag nanowires have been produced by Aternating Current (AC) electrodeposition in porous AAO template. So nanocompozit films consisting of regularly ordere Ag nanowires embedded in AAO templates. The composition and nanostructures of meterial was determined by SEM, XRD, EDX methods. The results of studying have showed nanocomposite Ag/Al2O3 demonstrated a stronger antibactericial activity than Al2O3 in air and water.